EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PROJECT BASED LEARNING (PjBL) DALAM MATA PELAJARAN INFORMATIKA TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMP KRISTEN CITRA BANGSA KUPANG - Celina fardiani onggong; Diana Yanni Ariswati Fallo; Maria magdalena Beatrice Sogen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Celina Fardiani Onggong, 2025 The Effectiveness of Project-Based Learning (Pjbl) in Informatics on the Learning Outcomes of Grade VII Students at Citra Bangsa Christian Junior High School, Kupang. Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang. Supervisors: Ms. Diana Y.A. Fallo, S.Kom., M.T. and Ms. Dr. Maria M.B. Sogen, S.Kom., M.Pd. This study focuses on the effectiveness of implementing a Project-Based Learning (PjBL) model in Informatics on the learning outcomes of seventh-grade students at Citra Bangsa Christian Middle School, Kupang. The objectives of the study were to determine how PjBL is applied to structured data and data processing applications, assess its effectiveness on learning outcomes, and demonstrate whether this model can improve student achievement. The study used a quantitative approach with a True Experimental Design. Data collection was conducted through two stages: a pretest before the lesson and a posttest after the lesson. The pretest was used to measure students' initial abilities, while the posttest measured improvement after the PjBL iimplementation. The results showed a significant improvement in student learning outcomes. The average pretest score for the experimental class was 69.11, increasing to 90.16 in the posttest. Meanwhile, the control class achieved an average pretest score of 52.28 and a posttest score of 83.83. Furthermore, questionnaire results from 37 students showed a percentage of 38.63%. These findings confirm that PjBL is effective in improving learning outcomes, as demonstrated by the significant difference between the experimental and control classes.